Pemberdayaan Masyarakat Melalui Gotong Royong Pembuatan Teba Modern: Upaya Meningkatkan Kesadaran Pengelolaan Sampah Organik di RT 26 RW 03 Kelurahan Betungan - Wulandari, Asyora; Riani, Gusti; Ramadhan, Rizky; Ulandari, Silvia; Kresnawati, Kresnawati; Fitriano, Yun; Soleh, Ahmad (Jurnal Dehasen Untuk Negeri, 2025)
Waste management issues, especially organic waste, are still a challenge in densely populated areas such as RT 26 RW 03 Kelurahan Betungan. Organic waste that is not managed properly can cause odor, disease, and pollute the environment. The community service program by Dehasen University students through "Dehasen for the Country" aims to increase public awareness of the importance of organic waste management through mutual cooperation activities and the creation of modern Shared Waste Bins (Teba). The activities were carried out with a participatory approach, actively involving residents from the planning stage to implementation. The Teba that was built was specifically designed to separate organic waste from other types of waste, and was equipped with educational information boards. The results of the activities showed increased community participation, the formation of habits of sorting organic waste, and the opening of opportunities for household compost processing. This program proves that community empowerment based on mutual cooperation is an effective strategy to encourage behavioral change in sustainable organic waste management.